ANALISIS INDIKATOR DISIPLIN PEGAWAI NEGERI SIPIL PADA KANTOR BUPATI KABUPATEN SAROLANGUN - Sylvia Kartika Wulan bhayangkari; Dahmiri Dahmiri; DianMala Fithriani Aira (Program Studi Manajemen Pemerintahan dan Keuangan Daerah Fakultas Ekonomi dan Bisnis Universitas Jambi, 2018)
This study aimed to find out the description of the discipline of Civil Servants at the Sarolangun District Bupati's Office and to analyze the discipline indicators of Civil Servants at the District Office of Sarolangun District. Research method used was survey research. The activity carried out was to examine using a questionnaire as a tool to collect data. Model In this study were observation and documentation method, and a questionnaire using Interval Scale and with a total of 107 participants. The method used was descriptive qualitative. The data analysis were carried out using a frequency research scale. Result showed that the employee discipline indicators at the Saroangun Regent's Office were influenced by several factors, namely goals and abilities, role models, remuneration, justice, referee, punishment, assertiveness, humanitarian relations. The indicator of employee work discipline at the Sarolangun District Head Office which had lowest value was factor of punishment sanctions that fall into the category of less discipline. Indicators of work discipline of employees which had highest value were the factors of goals and abilities categorized as discipline. Keywords: discipline, civil servants